2015
DOI: 10.1038/ncomms8464
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor antagonist-deficient mice develop autoimmune arthritis due to intrinsic activation of IL-17-producing CCR2+Vγ6+γδ T cells

Abstract: Interleukin-17 (IL-17)-producing γδ T (γδ17) cells have been implicated in inflammatory diseases, but the underlying pathogenic mechanisms remain unclear. Here, we show that both CD4+ and γδ17 cells are required for the development of autoimmune arthritis in IL-1 receptor antagonist (IL-1Ra)-deficient mice. Specifically, activated CD4+ T cells direct γδ T-cell infiltration by inducing CCL2 expression in joints. Furthermore, IL-17 reporter mice reveal that the Vγ6+ subset of CCR2+ γδ T cells preferentially prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 54 publications
(91 reference statements)
5
93
0
1
Order By: Relevance
“…The ‘ready‐to‐go’ phenotype of γδ 17 cells is especially efficient for early‐stage pathogen clearance. A combination of IL‐1 β and IL‐23, but not IL‐1 β or IL‐23 alone, is required to induce IL‐17 by γδ 17 cells 20. Further study revealed that IL‐23 is required for the induction of IL‐1R, and IL‐1 β is essential for the induction of IL‐17 20.…”
Section: The Mechanism Of Il‐17 Production In γδ17 Cellsmentioning
confidence: 95%
See 4 more Smart Citations
“…The ‘ready‐to‐go’ phenotype of γδ 17 cells is especially efficient for early‐stage pathogen clearance. A combination of IL‐1 β and IL‐23, but not IL‐1 β or IL‐23 alone, is required to induce IL‐17 by γδ 17 cells 20. Further study revealed that IL‐23 is required for the induction of IL‐1R, and IL‐1 β is essential for the induction of IL‐17 20.…”
Section: The Mechanism Of Il‐17 Production In γδ17 Cellsmentioning
confidence: 95%
“…However, because IL‐1 β alone does not induce IL‐17 production in Il1rn −/− mouse‐derived splenic γδ T cells20 and in normal peritoneum‐ and lung‐derived γδ T cells, in which high levels of IL‐1R are expressed,48 IL‐23 may play other roles than up‐regulating IL‐1R in the induction of IL‐17 expression in γδ T cells. In this context, ROR γ t expression is up‐regulated by IL‐1 β and IL‐23 in a synergistic manner 20. The inflammatory cytokine IL‐18,53 complement C5a,54 the ligand of Toll‐like receptors 1 and 2, and dectin‐155 also induce IL‐17 in collaboration with IL‐23.…”
Section: The Mechanism Of Il‐17 Production In γδ17 Cellsmentioning
confidence: 99%
See 3 more Smart Citations